The Application of the Al-Tasharruf Principle in Sharia Economic Law (Mu'âmalah Mâliyyah) - Adam Agus Putra, Panji; Eka Rahayu, Annisa (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2024)
Legal maxim (al-qawâ'id al-fiqhiyyah) have a function as a tool in carrying out the process of exploring and determining Islamic law. The laws that continue to develop along with the times are sharia economic law. The emergence of contemporary problems requires Islamic legal experts to respond to these problems. The rules of fiqh here have a significant role and function to solve the problems of sharia economic law. One of the economic problems that needs to be responded to is related to legal actions or what is called tasharruf. This research aims to understand the concept of tasharruf and its application in sharia economic law (mu'âmalah mâliyyah). The approach method in this research uses a normative juridical approach. This research is classified as library research and the type of data used is secondary data. The data analysis method in this research is qualitative. The results of the research show that using tasharruf, the ulama have formulated legal maxim. There are at least 5 (five) legal maxim related to tasharruf and these rules function as a basis for transaction activities and are relevant for application in sharia economic law activities.